ENHANCING INTERCULTURAL COMMUNICATIVE COMPETENCE IN TOURISM STUDENTS THROUGH TASK-BASED LANGUAGE TEACHING (TBLT) - Mahliyo Akhmedovna Bakhronova (TADQIQOTLAR.UZ, 2024)
This article explores the role of Task-Based Language Teaching (TBLT) in developing intercultural communicative competence (ICC) among tourism students. As the tourism industry increasingly requires professionals who can navigate multicultural environments effectively, the need for robust educational strategies that integrate language proficiency with intercultural skills has become paramount. The study outlines the theoretical underpinnings of ICC, emphasizing models by Byram and Deardorff, and aligns these with the principles of TBLT. Through a mixed-methods research design involving surveys, interviews, and classroom observations, the article demonstrates how TBLT can be implemented to enhance ICC in tourism education. The findings indicate that TBLT not only improves language skills but also significantly boosts students' intercultural awareness and sensitivity. Practical implications for curriculum design and pedagogical practices are discussed, offering educators a comprehensive framework to prepare students for the globalized tourism sector.